Pengaruh Pelatihan Teknologi Pertanian terhadap Produktivitas Petani di Program Pendidikan Vokasional Agribisnis - Bambang Irawan; Ihsan Mustofa; Nurleni Wahyuningsih; Gama Setyadi; Ade Rahmad Kurniawan (Bulletin of Community Engagement, 2021)
This study aims to examine the effect of agricultural technology training on farmer productivity within the context of the 2021 vocational agribusiness education program in Labuhan Ratu. The research employs a quantitative approach using explanatory research to explain causal relationships between variables through inferential statistical analysis. A total of 100 respondents were selected using the Slovin formula, and data were collected through a structured questionnaire. Data analysis included validity and reliability tests, t-test, and R² test using the Smart PLS software. The results show that agricultural technology training has a positive and significant effect on increasing farmer productivity, with a T-statistic value of 16.109 and a P-value of 0.000. These findings indicate that the higher the quality and intensity of training received, the greater the resulting agricultural productivity. The training not only enhances technical knowledge but also transforms behavior and improves farmers’ skills in adopting new technologies. Therefore, vocational agribusiness education plays a strategic role as a center for developing agricultural human resources that are responsive to technological advancements and the challenges of modern agriculture.